2010
DOI: 10.1007/s10815-010-9449-9
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor/c-Kit signaling in in vitro cultures supports early mouse embryonic development by accelerating proliferation via a mechanism involving Akt-downstream genes

Abstract: Purpose Stem cell factor (SCF)/c-Kit regulates the proliferation and survival of germ cells or stem cells; however, little is known about the role of SCF/c-Kit in preimplantation embryo development. Methods Using exogenous SCF supplementation and c-Kit siRNA injection, we investigated the role and mechanism of SCF/c-Kit in pre-implantation mouse embryos.Results Addition of soluble SCF to the culture medium improved blastocyst formation. c-Kit gene silencing reduced the rate of blastocyst formation and delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
13
0
3
Order By: Relevance
“…It has been recently shown that early onset-ofcleavage in human embryos is a predictor of normal development and high chance of live birth when compared with late onset-of-cleavage embryos in IVF/ICSI cycles [31]. Successful implantation of early cleaving embryos may be the result, among others, of a more optimal synchronization between embryonic development and the preparation of a receptive uterine environment [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that early onset-ofcleavage in human embryos is a predictor of normal development and high chance of live birth when compared with late onset-of-cleavage embryos in IVF/ICSI cycles [31]. Successful implantation of early cleaving embryos may be the result, among others, of a more optimal synchronization between embryonic development and the preparation of a receptive uterine environment [32].…”
Section: Discussionmentioning
confidence: 99%
“…SCF is highly expressed in oviducts and uterus through early pregnancy, demonstrating the prospect of paracrine signalling to the developing embryo (Arceci et al 1992). Addition of SCF improves blastocyst formation, and silencing c-kit reduces the kinetics of blastocyst formation indicating a proliferation-inducing effect (Lim et al 2010). Since both c-fms and c-kit are tyrosine kinases that activate similar signalling pathways, there is a high likelihood of cross-compensation between the two ligand-receptor systems.…”
Section: Colony Stimulating Factor-1 and Stem Cell Factormentioning
confidence: 99%
“…mTOR is considered as a crucial factor in cellular adaptive responses to energy, nutrients and growth factors in mammals (Cetrullo, D'Adamo, Tantini, Borzi, & Flamigni, 2015). Akt can activate mTOR, which regulates cell proliferation (Lim et al, 2010). In addition, ANXA8 upregulates the mRNA expression of vEGF, which is a key regulator of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%